PERBANDINGAN METODE MICROWAVE HYDRODISTILLATION (MH) DAN MICROWAVE HYDRODIFFUSION AND GRAVITY (MHG) UNTUK MENGEKSTRAK MINYAK ATSIRI DARI KULIT JERUK - Ayu Chandra Kartika Fitri; Fikka Kartika Widyastuti (Universitas Tribhuwana Tunggadewi Malang, 2017)
One source of essential oil that has long been popular is a citrus fruit (Citrus aurantium). Results waste citrus peel around 500,000 tonnes per year. So the prospects for the utilization of waste orange peel are big enough to extract the essential oil. However, conventional extraction methods have drawbacks in terms of product quality, so to find solutions to these shortcomings, it is necessary to use the extraction method by Microwave Hydrodiffusion and Gravity (MHG). This method combines the use of microwave heating and physical phenomena (hydrodiffusi and earth gravity) at atmospheric pressure, without addition of organic solvents or water. In this study used fresh orange peel material 400 and 500 grams, two variable microwave power of 100 and 300 Watt and the extraction time for 15, 30, 45 and 60 minutes. To know the processing time and the microwave power effective method of MHG, oil composition was analyzed by GCMS to determine the amount of the fraction of oxygenated compounds. The larger of installed microwave power, the higher of operating temperature, so the %yield increases in a shorter time. From the comparison of energy consumed, the MHG method is give 30% more energy efficient than the Microwave Hydrodistillation (MHD) method. The use of microwaves does not change the physical properties of oil. The oil produced from the MHG method has a good quality because it has specific gravity and refractive index values that meet the EOA quality standard and has a greater oxygenated compounds content than the MHD method